Importance of Neighborhood Aspect Ratio and Storm Climate to Adaptation Efforts to Reduce Coastal Flood Mortality - Zhang, Fanglin; Orton, Philip M. (Frontiers in Built Environment, 2022)
Low-lying Coastal Landfill Neighborhoods (CLaNs) often have a large coastline length relative to neighborhood width (aspect ratio) due to the common practice of reclaiming fringing wetlands along tidal waterways. Flood risk-reduction for CLaNs frequently involves elevated barriers, in the form of berms, seawalls or levees, which reduces risk but cannot completely eliminate residual risk (e.g., due to overtopping during extreme events). Managed retreat is an alternative approach for flood risk reduction, the general idea of which is to strategically ban development in hazard zones, relocate structures and/or abandon land. This study aims at exploring the tradeoffs between elevated barriers and managed retreat both in terms of CLaN aspect ratio and storm climate, for both short-term and long-term risk reduction with sea level rise. Hydrodynamic flood modeling of an idealized CLaN protected by different adaptation plans is used to simulate flood conditions and mortality for a range of storm surge amplitudes both for present-day and under different sea level rise scenarios. Results show that for a berm and a case of managed retreat of an equal cost, retreat becomes more beneficial than the berm in terms of mortality risk reduction for neighborhoods with a larger aspect ratio. We also find that berms are generally less effective for reducing mortality in regions with storms of a higher intensity. This study reveals the potential of idealized modeling to provide fundamental insights on the physical factors influencing the efficacy of different adaptation strategies for mortality risk reduction.